The response of quadrangular plates to blast load resulting from the detonation of encased buried charges. Issue 3 (September 2017) - Yuen, S Chung Kim; Warncke, DM
In real-life situation, especially in the numerous regions where conflicts exist, improvised explosive devices can be made of varying explosives encased in different containers detonated under varying conditions. This article reports on a series of experiments that was carried out to investigate the response of quadrangular plates to buried encased charges with a view to simulate the detonation of landmines buried in sand and compared with different loading conditions. Four loading scenarios, namely, bare and encased charges detonated in air and bare and encased charges buried under sand, were investigated. The results were evaluated and compared to the data obtained from bare charges detonated in air in terms of plate deformation and impulse imparted onto the target plate. A vertical ballistic pendulum was used to measure the impulse imparted onto the target plates by the different charges. The results showed that the presence of the steel casing in buried charge tests caused more damage to the test plate. An increase in the midpoint deflection of the test plate was observed despite a slightly reduced impulse imparted onto the plate. Larger impulse was imparted onto the target plate by buried bare charges compared to bare charges detonated in air. Midpoint deflection and impulse decreased with an increasing stand-off distance for all the different loading scenarios.